Meresponi Pemikiran John Duns Scotus Tentang Predestinasi dari Perspektif Reformed - Yoshua Ginting; Lorena Br Sembiring; Musa Sinar Tarigan (Universitas Pelita Harapan, 2026)
This study examines John Duns Scotus' views on the doctrine of predestination and analyzes them from the perspective of Reformed theology as formulated by John Calvin. Predestination is theological doctrine that continues to be debated because it is closely related to God's sovereignty in understanding the salvation of the elect and the rejected. Scotus, as a medieval scholastic theologian, emphasized predestination as an act of God's free and sovereign will to choose some people for salvation, without making God the cause of destruction. According to Scotus, human destruction occurs as result of human sin itself, not as direct decree from God. Conversely, Calvin understood predestination as God's eternal decision that determines both the salvation of the elect and the destruction of the non-elect, based entirely on God's will and sovereignty. This study uses literature review method by analyzing the major works of Scotus and Calvin as well as relevant theological sources. The results of the study show that there are differences between Scotus and Calvin in their understanding of the relationship between salvation and destruction, even though both affirm God's sovereignty in human salvation.